Risk Factors for Ischemic Heart Disease - Bisciglia, Andrea; Pasceri, Vincenzo; Irini, Diego; Varveri, Antonio; Speciale, Giulio (Reviews on Recent Clinical Trials, 2019)
Background: Several risk factors have been empirically linked to an increased risk of cardiovascular disease. Some of them are therapeutically amenable to modification; while others are not. Modifiable risk factors include physical inactivity, tobacco use, diet, “bad fats” in the blood, hypertension, and being overweight; while non-modifiable risk factors include the patient’s family history, the presence versus absence of diabetes mellitus, and demographic characteristics like age, gender, ethnicity, and socio-economic status. Methods: In this article, we review those risk factors that are both clinically important and amenable to change. Conclusion: To prevent cardiovascular disease, it is important to minimize modifiable risk factors, like LDL cholesterol.
Keywords: LDL cholesterol